Penerapan Pursed Lips Breathing (PLB) untuk Perubahan Saturasi Oksigen Pada Anak dengan Gangguan Sistem Pernafasan Akibat Bronchopneumonia di RSUD dr. Soekardjo Kota Tasikmalaya - Novi Rosuliana; Dhea Mutia Anggreini (STIKES dan AKZI Karya Husada Kediri, 2023)
Bronchopneumonia is inflammation of the wall bronchioles and surrounding lung tissue. The purpose of writing this scientific paper is to provide an overview of nursing care by applying Pursed Lips Breathing (PLB) for changes in oxygen saturation in children with respiratory system disorders due to bronchopneumonia. The research method of this scientific paper is descriptive qualitative in the form of participatory observation. The process of providing nursing care and implementing pursed lips bretahing is carried out for 3 days. This study was conducted on 2 children who had bronchopneumonia. The results of the overall evaluation that the action of PLB is very influential in increasing oxygen saturation in children with bronchopneumonia. The next research advice is to be able to pay more attention to the problems experienced by clients, especially being able to establish relationships between the involvement of patients, families, and other health teams so that the implementation of nursing implementation can run optimally.